Health status and public health education for internal older migrants in China: Evidence from a nationally representative survey - Zeng, Wen; Wang, Cui; Chen, Hongbo; Tong, Beibei; Li, Dan; Zou, Ziqiu; Liu, Peiyuan; Yao, Yuanrong; Shang, Shaomei (Frontiers in Public Health, 2022)
Background Self-rated health has been widely used as a useful screening tool to subjectively evaluate individuals' health status. Under the context of the rapid growth of aging, there was a dramatic rapid expansion in internal older migrants in China. Serious concerns on the issues of health status continue to attract quite a lot of attention over the past decades. Public health education is one of the most important health care services and methods to improve individuals' health status. However, most previous studies focus on the utilization of public health services such as visiting to doctors, physical examination, and hospitalization. There was limited evidence on the self-rated health and public health education of older migrants. Objectives The study aimed to evaluate self-rated health and the associated determinants in older migrants, as well as to gain a deeper insight into the current status of public health education received by older migrants. Methods We derived the data from the National Migrants Population Health and Family Planning Dynamic Monitor Survey 2018, a cross-sectional study, for secondary analysis. Internal migrants aged 60 years old or over were included in the study. Self-rated health was the dependent variable, while sociodemographic characteristics were the independent variable. The univariate and multivariate analyses were performed by Stata 15.1. Results A total of 5,589 older migrants were included in the study. Eighty-two percentage of older migrants reported healthy self-rated health. There was a significant association between age, gender, minzu, education level, monthly income, public health education, and self-rated health (P < 0.5). However, the proportion of older migrants that received specific public health education was <50%. The most common approach to receiving public health education was through the leaflet, while <20% of older migrants received public health education through public consultation and one-to-one education. Conclusions It was necessary to promote the publicity of public health education in older migrants through easy access and diverse approaches in order to effectively spread health-related knowledge to older migrants to satisfy their health needs and maintain their health.